The Elements of Unlawful Acts as the Basis for Lawsuits in Land Disputes - Bicar Maruli Tua Sianturi; Djoko Setyo Hartono Widagdo (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2022)
This research aims to know the community relations if one party has violated a right and harmed another party, if it cannot be resolved amicably to provide compensation, then the party whose rights have been violated and suffered a loss can file a lawsuit to court on the grounds that there has been a violation of law carried out by other parties accompanied by accurate evidence. For a claim to be submitted to the court so that it can be accepted and granted by the judge, the reasons used as the basis for the claim must be clear and contain elements of a violation of the law. Another aims to obtain data about judges' considerations in deciding a case that falls under the qualification of unlawful acts. This research used a normative legal research with statutory and conceptual approaches. The result show the judge's consideration in deciding to grant part of the lawsuit filed by the Plaintiff because the witness evidence submitted by the Plaintiff can legally prove that the plaintiff is the legal owner of the object of the case and what is alleged in the plaintiff's lawsuit that the defendant committed an unlawful act, is it true or not? what the Defendant did complied with the elements of an unlawful act and the Defendant was unable to prove reasonable evidence.